Designing a New Cement Composition Using Agricultural Wastes for Underground Gas Storage - Abid, Khizar (Curtin University, 2018)
To reinforce cement against the attack of supercritical CO2 in a storage site, agricultural wastes (POFA and RHA) and Nano particles (Nano Silica) were used. Post-carbonation tests of agricultural wastes and Nano Silica based cement were done according to the API standard and it was found that almost all samples have a lesser carbonated area then the neat cement except 5 wt% POFA. Nano Silica based cement seem to be the best choice.